The Role of Transformational Leadership in Improving Employee Performance in Indonesian Companies - Rosmaria (TechTalent & Business Review, 2025)
This article examines the role of transformational leadership in improving employee performance in companies in the archipelago. Transformational leadership, which involves the ability of leaders to inspire, motivate, and encourage innovation, is expected to address the unique challenges faced by companies in the region. This study uses a case study method to explore how transformational leaders influence individual motivation, commitment, and performance across various industrial sectors in Indonesia. The results show that transformational leadership significantly contributes to improving employee performance through increased job satisfaction, clear goal setting, and skill development. These findings provide practical insights for managers in the archipelago to adopt leadership styles that can motivate and empower their employees in the face of changing market dynamics.